miR397/Laccase Gene Mediated Network Improves Tolerance to Fenoxaprop-P-ethyl in Beckmannia syzigachne and Oryza sativa - Pan, Lang; Zhao, Hongwei; Yu, Qin; Bai, Lianyang; Dong, Liyao (Frontiers in Plant Science, 2017)
Herbicide resistance can be either target-site or non-target-site based. The molecular mechanisms underlying non-target-site resistance (NTSR) are poorly understood, especially at the level of gene expression regulation. MicroRNAs (miRNAs) represent key post-transcriptional regulators of eukaryotic gene expression and play important roles in stress responses. In this study, the miR397 gene from Beckmannia syzigachne (referred to as bsy-miR397) was functionally characterized to determine its role in regulating fenoxaprop-P-ethyl resistance. We showed that (1) bsy-miR397 transcript level is constitutively higher in resistant than in sensitive B. syzigachne plants, whereas bsy-Laccase expression and activity show the opposite trend, and (2) bsy-miR397 suppresses the expression of bsy-Laccase in tobacco, indicating that it negatively regulates bsy-Laccase at the transcriptional level. We found evidences that miR397/laccase regulation might be involved in fenoxaprop-P-ethyl NTSR. First, the rice transgenic line overexpressing OXmiR397 showed improved fenoxaprop-P-ethyl tolerance. Second, following activation of bsy-Laccase gene expression by CuSO4 treatment, fenoxaprop resistance in B. syzigachne tended to decrease. Therefore, we suggest that bsy-miR397 might play a role in fenoxaprop-P-ethyl NTSR in B. syzigachne by down-regulating laccase expression, potentially leading to the enhanced expression of 3 oxidases/peroxidases genes to introduce an active moiety into herbicide molecules in Phase-2 metabolism. Bsy-miR397, bsy-Laccase, and other regulatory components might form a regulatory network to detoxify fenoxaprop-P-ethyl in B. syzigachne, supported by the differential expression of transcription factors and oxidases/peroxidases in the rice transgenic line overexpressing OXmiR397. This implies how down-regulation of a gene (laccase) can enhance NTSR. Our findings shed light on the daunting task of understanding and managing complex NTSR in weedy plant species.